Efektivitas E-Modul Pendidikan Multikultural Dalam Meningkatkan Nilai Karakter Berkebhinekaan Global Siswa Sekolah Dasar Negeri 8 Suwawal - Muh Muhaimin; Efendi, Abdullah; Fitria, Bella; Malika, Najma (Jurnal Penelitian dan Pendidikan IPS, 2024)
This study aims to analyze the effectiveness of a multicultural education e-module in enhancing students' global diversity character values at Sekolah Dasar Negeri 8 Suwawal. The scope of the research includes understanding and internalizing values of tolerance, mutual respect, and cross-cultural collaboration through the use of technology in the learning process. The study employs a quasi-experimental method with a pretest-posttest design involving two groups: an experimental group using the e-module and a control group employing conventional methods. Data were analyzed using a Paired Samples T-Test to determine the significance of differences between pretest and posttest results. The findings indicate a significant difference between the mean pretest and posttest scores, with a p-value of 0.040 (p < 0.05), suggesting that the use of the multicultural e-module significantly improves students' global diversity character values. The effect size measured using Cohen's d is 0.507, indicating a medium effect. However, the mean difference of 3.26 reflects some uncertainty due to the insufficient sample size. In conclusion, the multicultural e-module is effective in enhancing students' global diversity character values. Nevertheless, further research with a larger sample size is required to ensure more accurate results and broader generalization.